PENGUATAN PENTINGNYA LANJUT STUDI KE PERGURUAN TINGGI BAGI ANAK PEKERJA MIGRAN INDONESIA DI KOTA KINABALU - Mahyuddin, Mahyuddin; Nurkidam, A.; Pikahulan, Rustam M.; Umaima, Umaima; Mustary, Emilia; Nurhakki, Nurhakki; Pradana, Syafaat Anugrah; Arqam, Arqam; Shah, Jalihah MD (Archipelago, 2023)
ABSTRACTThe educational problems of children of Indonesian migrant workers who attend the Kota Kinabalu Indonesian School (SIKK) generally revolve around the problem of them not continuing their education to graduate level. This happens because they do not have university references and limited access to information to be able to continue their studies. More SIKK students come from Eastern Indonesia, specifically South and West Sulawesi. This encourages community service groups to carry out community service programs in Kinabalu City, Malaysia. This activity needs to be carried out to increase public knowledge, especially children of Indonesian migrant workers, about the importance of continuing their studies at university and to provide information about scholarship services. The service process is carried out in 3 stages, namely planning, implementation and evaluation. This activity went smoothly and was well received by the Indonesian Consulate General in Kinabalu City, SIKK and the Children of Indonesian Migrant Workers